PRESCHOOL CHILDREN’S CREATIVE DEVELOPMENT OF PRACTICAL ART METHODS - Atamanchuk, Nina; Yalanska, Svetlana; Tur, Oksana (PSYCHOLOGICAL JOURNAL, 2020)
The article presents the theoretical analysis and empirical research on preschool children’s creative development by means of art. We are convinced that art practices as an innovative technology should be used in order to develop children’s abilities and creativity, the creativity of adults working with children. After all, the basis of art practices is art as an activity that reveals the reality in specific sensory images. We have determined that the productive activities that are most interesting for preschool children are drawing and fairy-tale situations. The empirical study used drawing and fairy-tale techniques. We selected and described the art practices to be used in work with preschool children with the aim to develop such qualities as observation, attention, memory, imagination, fantasy. These qualities contribute to the development of preschool children’s independent creative activities, which form all the best human qualities and reveal their, often hidden, talents, skills and abilities. The children from the experimental group showed more creative elements and did it clearly during tasks solving compared to the control group. They offered more original options in addition to the standard vision of objects and phenomena. Modern preschool children are characterized by decreased activity, poorer imagination. Preschoolers’ creative development lags far behind their peers from the previous century. In addition, modern children have either high or low creative development (only few children showed medium development). Children’s awareness of modern electronic devices makes them dependent on gadgets, computers and television. At the same time, the number of gifted children has increased dramatically, as well as indigo children, who are characterized by super-abilities and changes in their psyche. All these facts point to problems and contradictions existing at modern older preschoolers. Participating in art practices, preschool children can reveal their potential for the development of their creativity. Children learn to solve various creative tasks, express themselves artistically and develop hidden talents. Art promotes children’s abilities, motives, knowledge and skills, so that they create something new, original, unique. The proposed art practices opens the space for educators, psychologists at children’s educational institutions to develop children’s creativity, because humanity has not yet invented a better creative tools than fairy tales, drawing, games, stories. From the first years of life, children have a natural need to show their own uniqueness, individuality, to reveal their talents and creative abilities. In kindergarten, children love to draw, sing, dance, having great fun. There is no doubt that art is the language of children’s souls. It is an efficient tool for the development of preschooler’s abilities, skills and creativity. Art practice for preschool children is an interesting and bright game.